Effects of short‐term oral corticosteroid intake on dietary intake, body weight and body composition in adults with asthma – a randomized controlled trial. Issue 5 (May 2015) - Berthon, B. S.; Gibson, P. G.; McElduff, P.; MacDonald‐Wicks, L. K.; Wood, L. G.
Summary Background Oral corticosteroids (OCS) are an efficacious treatment for asthma exacerbations, yet risk of adverse effects may decrease patient adherence to therapy. In particular, changes in appetite and dietary intake, which lead to weight gain and changes in body composition, are considered undesirable. Objective To determine whether 10‐day OCS therapy in adults with asthma causes changes in leptin, appetite, dietary intake, body weight and body composition. Methods Double‐blinded, placebo‐controlled randomized cross‐over trial of 10 days prednisolone (50 mg) in adults with stable asthma (n = 55) (ACTRN12611000562976). Pre‐ and post‐assessment included spirometry, body weight, body composition measured by dual‐energy X‐ray absorptiometry and bioelectrical impedance analysis, appetite measured using a validated visual analogue scale (VAS) and dietary intake assessed using 4‐day food records. Leptin was measured as a biomarker of appetite and eosinophils as an adherence biomarker. Outcomes were analysed by generalized linear mixed models. Results Subject adherence was confirmed by a significant decrease in blood eosinophils (× 109/L) following prednisolone compared to placebo [Coef. −0.29, 95% CI: (−0.39, −0.19) P < 0.001]. There was no difference in serum leptin (ng/mL) [Coef. 0.13, 95% CI: (−3.47, 3.72) P = 0.945] or appetite measured by VAS (mm) [Coef. −4.93, 95% CI: (−13.64, 3.79) P = 0.267] following prednisolone vs. placebo. There was no difference in dietary intake (kJ/day) [Coef. 255, 95% CI: (−380, 891) P = 0.431], body weight (kg) [Coef. −0.38, 95% CI: (−0.81, 0.05) P = 0.083] or body fat (%) [Coef. −0.31, 95% CI: (−0.81, 0.20) P = 0.230]. Symptoms including sleep and gastrointestinal disturbance were reported significantly more often during prednisolone vs. placebo. Conclusions and Clinical Relevance Short‐term OCS in stable asthma did not induce significant changes in appetite, dietary intake, body weight or composition, although other adverse effects may require medical management. This evidence may assist in increasing medication adherence of asthmatics prescribed OCS for exacerbations.